Review of Literature: Business Sustainability Essentials For Business Startup - Irawan, Edi; Winarno, Agung; Pratikto, Heri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This literature review discusses research related to business model innovation and startup sustainability. The review shows that business model innovation plays an important role in increasing profits and value creation, which also helps startups survive in a dynamic business environment. Sustainable business models, concepts such as a business approach that emphasizes ethical practices and accountability in addressing social, environmental, and economic impacts, consumer awareness and technological innovation play an important role. The importance of the elements of an eco-conscious approach to business operations, particularly in light of the fierce competition and significant transformations shaping the food industry. These elements include client segments, the connections and interactions a business maintains with its customers to build loyalty and trust., key activities, key resources, partner network and cost structure. With regard access to resources and activities that involve the use of innovative, distinctive, and eco-friendly raw materials, along with certain assets, can ensure high-quality products with low environmental impact